Clinical Subtypes of Dementia with Lewy Bodies Based on the Initial Clinical Presentation. - Morenas-Rodriguez, Estrella; Sala, Isabel; Subirana, Andrea; Pascual-Goñi, Elba; Sánchez-Saudinós, Ma Belén; Alcolea, Daniel; Illán-Gala, Ignacio; Carmona-Iragui, María; Ribosa-Nogué, Roser; Camacho, Valle; Blesa, Rafael; Fortea, Juan; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Dementia with Lewy bodies (DLB) is a heterogeneous disease in which clinical presentation, symptoms, and evolution widely varies between patients. OBJECTIVE: To investigate the existence of clinical subtypes in DLB based on the initial clinical presentation. METHODS: 81 patients with a clinical diagnosis of probable DLB were consecutively included. All patients underwent a neurological evaluation including a structured questionnaire about neuropsychiatric symptoms and sleep, an assessment of motor impairment (Unified Parkinson Disease Rating Scale subscale III), and a formal neuropsychological evaluation. Onset of core symptoms (hallucinations, parkinsonism, and fluctuations) and dementia were systematically reviewed from medical records. We applied a K-means clustering method based on the initial clinical presentation. RESULTS: Cluster analysis yielded three different groups. Patients in cluster I (cognitive-predominant, n = 46) presented more frequently with cognitive symptoms (95.7%, n = 44, p < 0.001), and showed a longer duration from onset to DLB diagnosis (p < 0.001) than the other clusters. Patients in cluster II (neuropsychiatric-predominant, n = 22) were older at disease onset (78.1±5 versus 73.6±6.1 and 73.6±4.2 in clusters I and III, respectively, both p < 0.01), presented more frequently with psychotic symptoms (77.3%, n = 17), and had a shorter duration until the onset of hallucinations (p < 0.001). Patients in cluster III (parkinsonism-predominant, n = 13) showed a shorter time from onset to presence of parkinsonism (p < 0.001) and dementia (0.008). CONCLUSIONS: Three clinical subtypes of DLB can be defined when considering the differential initial presentations. The proposed subtypes have distinct clinical profiles and progression patterns.

Diagnostic and Prognostic Value of the Combination of Two Measures of Verbal Memory in Mild Cognitive Impairment due to Alzheimer's Disease. - Sala, Isabel; Illán-Gala, Ignacio; Alcolea, Daniel; Sánchez-Saudinós, Ma Belén; Salgado, Sergio Andrés; Morenas-Rodriguez, Estrella; Subirana, Andrea; Videla, Laura; Clarimón, Jordi; Carmona-Iragui, María; Ribosa-Nogué, Roser; Blesa, Rafael; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Episodic memory impairment is the core feature of typical Alzheimer's disease. OBJECTIVE: To evaluate the performance of two commonly used verbal memory tests to detect mild cognitive impairment due to Alzheimer's disease (MCI-AD) and to predict progression to Alzheimer's disease dementia (AD-d). METHODS: Prospective study of MCI patients in a tertiary memory disorder unit. Patients underwent an extensive neuropsychological battery including two tests of declarative verbal memory: The Free and Cued Selective Reminding Test (FCSRT) and the word list learning task from the Consortium to Establish a Registry for Alzheimer's disease (CERAD-WL). Cerebrospinal fluid (CSF) was obtained from all patients and MCI-AD was defined by means of the t-Tau/Aβ1-42 ratio. Logistic regression analyses tested whether the combination of FCSRT and CERAD-WL measures significantly improved the prediction of MCI-AD. Progression to AD-d was analyzed in a Cox regression model. RESULTS: A total of 202 MCI patients with a mean follow-up of 34.2±24.2 months were included and 98 (48.5%) met the criteria for MCI-AD. The combination of FCSRT and CERAD-WL measures improved MCI-AD classification accuracy based on CSF biomarkers. Both tests yielded similar global predictive values (59.9-65.3% and 59.4-62.8% for FCSRT and CERAD-WL, respectively). MCI-AD patients with deficits in both FCSRT and CERAD-WL had a faster progression to AD-d than patients with deficits in only one test. CONCLUSIONS: The combination of FCSRT and CERAD-WL improves the classification of MCI-AD and defines different prognostic profiles. These findings have important implications for clinical practice and the design of clinical trials.